Analysis of the Development Needs of HOTS-Based Electronic Student Worksheets with Culturally Responsive Teaching Approach in Elementary Schools - Adita Dwi Safirah; Nasution Nasution; Utari Dewi (IJORER : International Journal of Recent Educational Research, 2024)
Objective: To address this issue, this research explores the integration of HOTS with the Culturally Responsive Teaching approach in developing Electronic Student Worksheets as a holistic and relevant learning solution. This research analyzes the preliminary development of HOTS-based electronic Student Worksheets with a Culturally Responsive Teaching Approach. Method: This research adopts a qualitative descriptive approach and involves fourth-grade teachers in Pasuruan Regency as research subjects. Sampling is done through purposive sampling. Data collection includes observation, documentation, and interviews. Results: The research begins with a preliminary study to identify the foundations that strengthen the development of electronic Student Worksheets. Then, a field study is conducted by directly observing the teaching materials teachers use in their instruction. Curriculum analysis focuses on Student Worksheets and learning materials. The Student Worksheets teachers use need to integrate HOTS and the Culturally Responsive Teaching approach. This preliminary study findings suggest the need for developing HOTS-based electronic Student Worksheets with a Culturally Responsive Teaching approach so that students can improve their critical thinking skills, learn about the culture of their local area, and appreciate both their own culture and the cultures of others. Novelty: This research implies that implementing HOTS with the Culturally Responsive Teaching approach in elementary education can provide a solid foundation for producing students who are not only academically intelligent but also possess character, critical thinking skills, and an understanding and appreciation of cultural diversity.